SOCIAL CONFLICT AND COMMUNITY FRAGMENTATION: A STUDY IN NEGERI HAYA, TEHORU DISTRICT, CENTRAL MALUKU REGENCY - Muhammad Rahman Abdullah Namakule; Tonny Donald Pariela; Jeffry EM Leiwakabessy (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study examines the dynamics of social conflict and community fragmentation in Negeri Haya, Tehoru District, Central Maluku. The conflict arose from the entry of a company conducting granite sand extraction without proper mining permits, creating tensions between customary institutions, local government, and community members. Differences in understanding regarding licensing, authority, and economic interests led to disagreements and gradually escalated into open conflict. The study employed qualitative descriptive methods, including in-depth interviews, field observations, and document analysis, to explore the background, forms, processes, and impacts of the conflict. Findings indicate that the conflict significantly affected community livelihoods, social relationships, and trust among residents, while also dividing the community into opposing groups. Efforts at social reconciliation were carried out through customary sanctions, government mediation, and collective community initiatives to restore harmony. The study highlights the importance of integrating institutional, customary, and community-based approaches in managing resource-related conflicts in indigenous settings.